Upaya Restorasi Lahan Melalui Pembagian Bibit Tanam di Dusun Tambes Desa Lerpak Geger Bangkalan - Fatichatus Sadiyah; Abdurrohman Abdurrohman (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Tambes Hamlet is known for its fertile soil and rich natural potential. This land supports the growth of various crops and provides opportunities for farmers. With a good climate and abundant resources, Tambes Hamlet can produce a lot of agricultural products, supporting food needs and the local economy. However, these resources have not been utilized to their full potential, with a lot of empty land and a lack of fruit commodities. Lack of agricultural management knowledge is the main reason for the difficulties faced by farmers. The author conducts land restoration to improve soil quality and farmer knowledge, and works with the government to provide education and distribute planting seeds. These efforts benefit both the environment and the community. In general, in implementing this program, the author divides it into three methods; preparation, implementation, and evaluation. Land restoration is an important process to repair damaged land. The goal is to return the land to a better condition so that it can be used for agriculture or other ecosystems. Restoration methods include reforestation, which is the replanting of trees. Soil conservation is also important to maintain fertile soil quality. Restoration benefits the environment and the community, increasing biodiversity and supporting plant and animal species. Tambes Hamlet faces soil productivity issues that affect agriculture. Soil restoration is needed so that the community can benefit from it.